2021
DOI: 10.3390/molecules26113067
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Functionalized Graphene Oxide Nanoparticles Loaded with Nigella sativa Extract: A Smart Antibacterial Therapeutic Drug Delivery System

Abstract: Flaky graphene oxide (GO) nanoparticles (NPs) were synthesized using Hummer’s method and then capped with polyethylene glycol (PEG) by an esterification reaction, then loaded with Nigella sativa (N. sativa) seed extract. Aiming to investigate their potential use as a smart drug delivery system against Staphylococcus aureus and Escherichia coli, the spectral and structural characteristics of GO-PEG NPs were comprehensively analyzed by XRD, AFM, TEM, FTIR, and UV- Vis. XRD patterns revealed that GO-PEG had diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 32 publications
7
59
0
Order By: Relevance
“…NPs interact with cellular organelles and biomolecules such as DNA, enzymes, ribosomes, and lysosomes, influencing cell membrane permeability, protein activation, gene expression, and oxidative stress [48]. In the current study, PEG/TiO 2 (2) was effective against all tested bacterial strains, in close agreement with other previous works [86,87]. As PEG/TiO 2 NPS are smaller in size, they are expected to have a better chance of interacting with bacteria or better access to endogenous bacterial proteins.…”
Section: Antimicrobial Performance Evaluationsupporting
confidence: 91%
“…NPs interact with cellular organelles and biomolecules such as DNA, enzymes, ribosomes, and lysosomes, influencing cell membrane permeability, protein activation, gene expression, and oxidative stress [48]. In the current study, PEG/TiO 2 (2) was effective against all tested bacterial strains, in close agreement with other previous works [86,87]. As PEG/TiO 2 NPS are smaller in size, they are expected to have a better chance of interacting with bacteria or better access to endogenous bacterial proteins.…”
Section: Antimicrobial Performance Evaluationsupporting
confidence: 91%
“…We provided Table 2 to show a comparison between our research with similar studies. 37,45–48 As can be seen, the newly prepared nanocomposite including NiFe 2 O 4 @MIL-101(Fe)/GO had a satisfactory drug loading percentage, drug release, and also antibacterial activities in comparison with previous structures.…”
Section: Resultsmentioning
confidence: 81%
“…Thus, the results of this study indicate that the generated NPs (Au, ZnO, Cur, Au@ZnO NPs, and Cur-Au@ZnO) mediate the adherence and invasion of S. aureus strain in REF cells. Likewise, a study by Jihad et al [ 44 ] reported that the pretreated REF cells with graphene oxide nanoparticles capped with polyethylene glycol (PEG) and loaded with Nigella sativa (GONPs, GONPs-PEG, and GONPs-PEG- N. sativa ) at a concentration of 100 μ g/mL can delay the invasion of different types of Gram-negative and positive bacterial strains. Taken together, the present study verified that the investigated NPs play a mediation role in the adherence and invasion of S. aureus to REF cells.…”
Section: Resultsmentioning
confidence: 99%
“…10 μ L was taken from each well and applied to the nutrient agar, where bacterial cells grew and counted after 20 h. The average bacterium from each well was used to calculate the invasion potential of bacteria. This assay was carried out in triplicate [ 44 ].…”
Section: Methodsmentioning
confidence: 99%